Associations of medical comorbidity, psychosis, pain, and capacity with psychiatric hospital length of stay in geriatric inpatients with and without dementia. (21st October 2014) - Ismail, Zahinoor; Arenovich, Tamara; Granger, Robert; Grieve, Charlotte; Willett, Peggie; Patten, Scott; Mulsant, Benoit H
ABSTRACT: Background: Geriatric psychiatry hospital beds are a limited resource. Our aim was to determine predictors of hospital length of stay (LOS) for geriatric patients with dementia admitted to inpatient psychiatric beds. Methods: Admission and discharge data from a large urban mental health center, from 2005 to 2010 inclusive, were retrospectively analyzed. Using the resident assessment instrument - mental health (RAI-MH), an assessment that is used to collect demographic and clinical information within 72 hours of hospital admission, 169 geriatric patients with dementia were compared with 308 geriatric patients without dementia. Predictors of hospital LOS were determined using a series of general linear models. Results: A diagnosis of dementia did not predict a longer LOS in this geriatric psychiatry inpatient population. The presence of multiple medical co-morbidities had an inverse relationship to length of hospital LOS – a greater number of co-morbidities predicted a shorter hospital LOS in the group of geriatric patients who had dementia compared to the without dementia study group. The presence of incapacity and positive psychotic symptoms predicted longer hospital LOS, irrespective of admission group (patients with dementia compared with those without). Conversely, pain on admission predicted shorter hospital LOS. Conclusions: Specific clinical characteristics generally determined at the time of admission are predictive of hospital LOS in geriatric psychiatry inpatients. Addressing these factors early on during admission and in the community may result in shorter hospital LOS and more optimal use of resources.